Investigation of factors affecting annual milk yield of different goat breeds using panel data analysis - Esra Yavuz (PLoS ONE, 2026)
This study aims to evaluate the effects of basic biological factors such as age and lactation length on milk yield by examining the annual milk yield data of five different goat breeds (Damaskus, Pure Damaskus, Toros, Çukurova, and German Fawn) raised in Turkey between 1991 and 1997. The study used a panel data analysis method that takes into account both horizontal (between races) and vertical (within time) variability. It includes annual milk yield (liters), lactation period (days), and age (years) variables of randomly selected individuals from each race. Fixed effects and random effects models were compared in the statistical analysis, and the fixed effects model was preferred according to the Hausman test results. The findings revealed that both age and lactation period had positive and statistically significant effects on milk yield. In addition, significant differences were found among the breeds in terms of milk yield; it was observed that the Çukurova breed had higher performance, while the Toros breed had lower milk yield. In conclusion, this study shows that breed selection and production management play a critical role in productivity in goat breeding and reveals that panel data analysis can be used as an effective method in animal production research.